The achievements and developments in Hungarian crime scene investigation (Academic Journal of Internal Affairs, 2016)
The author provides an overview of the integration of the crime scene services in the Hungarian National Institute for Forensic Sciences (HIFS).
Keywords: crime; HIFS; Hungary